The evolving role of novel and next generation therapies in the management of multiple myeloma: introduction and current therapies 1 - Richardson, Paul G. (Henry Stewart Talks, 2019)
Multiple myeloma and key targets in 2019, Principles of initial therapy in stem cell transplant, Therapeutics and drug agents used in Multiple Myeloma